High-strength low-temperature co-fired ceramic material and water-based tape casting preparation method thereof

Through the water-based casting preparation method, combining the mixture of high-strength alumina ceramic powder, silicon nitride ceramic powder, alumina fiber and BBSCA glass powder, the problem of insufficient mechanical strength of low-temperature co-fired ceramic materials is solved, and high-quality preparation is made Ceramic materials with bending strength, good thermal conductivity and matching thermal expansion properties are suitable for electronic packaging.

CN119504235APending Publication Date: 2025-02-25HEFEI INSTITUTE OF PHYSICAL SCIENCE CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411277943.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The mechanical strength of existing low-temperature cofired ceramic materials is insufficient, making it difficult to meet the mechanical reliability requirements of electronic products under stress and drop impacts.

Method used

By using water-based casting molding preparation method, high-strength alumina ceramic powder, silicon nitride ceramic powder, alumina fibers and BBSCA glass powder are mixed with water, dispersant, plasticizer, binder and defoaming. The agent is made into a homogeneous slurry by ball milling. After defoaming, casting and drying, it is subjected to vacuum hot pressing solid phase sintering to obtain high-strength low-temperature co-fired ceramic material.

Benefits of technology

The preparation of high-strength, low-temperature co-fired ceramic materials has been achieved, with a bending strength in the range of 220-420MPa, a thermal conductivity coefficient of 5-11W/(m·K), and a thermal expansion coefficient matching silicon components, which is suitable for electronic packaging materials and their manufacturing fields. At the same time, using water as the only solvent reduces production costs, reduces environmental pollution and harm to human health.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005040794630000061
    Figure BDA0005040794630000061
  • Figure BDA0005040794630000071
    Figure BDA0005040794630000071
Patent Text Reader

Abstract

The invention belongs to the field of low-temperature co-fired ceramic materials, and particularly relates to a high-strength low-temperature co-fired ceramic material and a water-based tape casting preparation method thereof. The preparation method comprises the following steps: mixing high-strength aluminum oxide ceramic powder, silicon nitride ceramic powder, aluminum oxide fibers and glass powder by taking water as a unique solvent in a tape casting process, adding water and a dispersing agent, performing ball milling, adding a plasticizer, a binder and a defoaming agent, and continuing ball milling to prepare uniform slurry suitable for tape casting; a uniform and smooth cast film is prepared after defoaming, casting and drying, and the high-strength low-temperature co-fired ceramic material can be obtained after vacuum hot-pressing solid-phase sintering. The method is simple to operate, low in cost, non-toxic, harmless and environment-friendly, and conditions are easy to control. The bending strength of the prepared low-temperature co-fired ceramic material ranges from 220 MPa to 420 MPa, the heat conductivity coefficient ranges from 5 W / (m.K) to 11 W / (m.K), the thermal expansion coefficient is matched with the thermal expansion coefficient of a silicon component, and the low-temperature co-fired ceramic material has great application prospects in the fields of electronic packaging materials and manufacturing of the electronic packaging materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of low-temperature co-fired ceramic materials, and in particular relates to a high-strength low-temperature co-fired ceramic material and a water-based tape-casting preparation method thereof. Background Art

[0002] Low temperature co-fired ceramic (LTCC) is an integrated ceramic multilayer material that is made by printing interconnected conductors, components and circuits on unsintered cast films, and then laminating and pressing the structure together and sintering it. It can package the three major passive devices (resistors, capacitors, inductors) and various other passive devices such as filters and transformers in a multi-layer wiring substrate, and integrate them with active devices into a complete circuit system. Due to its excellent dielectric, thermal and mechanical properties, it can meet the needs of continuous miniaturization, high integration and low cost of electronic components.

[0003] Low-temperature co-fired ceramics using a glass / ceramic composite system have the advantages of easy performance control and simple preparation process. The layered structure design can improve its space utilization and achieve high integration of the circuit system. LTCC materials have solved the problem of miniaturization and integration of electronic components to a certain extent with their excellent dielectric and thermal properties. However, a key factor currently limiting the miniaturization of electronic products is the mechanical strength of the packaging material itself. In order to ensure mechanical reliability and resist stress and drop impact, when the mechanical strength of the device reaches its limit through structural design, it is necessary to increase the mechanical strength of the LTCC material itself to meet the application requirements. Summary of the invention

[0004] The purpose of the present invention is to provide a water-based tape-casting preparation method for high-strength, low-temperature co-fired ceramic materials. The preparation method uses water as the only solvent in the tape-casting process, mixes high-strength alumina ceramic powder, silicon nitride ceramic powder, alumina fiber and glass powder, adds water and a dispersant and then ball-mills them, then adds a plasticizer, a binder and a defoaming agent and continues to ball-mill them to make a uniform slurry suitable for tape-casting, and after degassing, tape-casting and drying, a uniform and smooth tape-cast film is obtained, and after vacuum hot pressing solid-phase sintering, a high-strength, low-temperature co-fired ceramic material can be obtained.

[0005] To achieve the above object, the present invention adopts the following technical solution: a water-based tape-casting preparation method of a high-strength low-temperature co-fired ceramic material, comprising the following steps:

[0006] S1. Weigh bismuth trioxide, boron oxide, silicon dioxide, copper oxide and aluminum oxide in a molar ratio of 1:(0.1-1):(0.1-1):(0.4-1):(0.1-0.5), mix and ball-mill evenly, then keep at 600-800° C. for 1-4 h, and ball-mill into powder after natural cooling to obtain BBSCA glass powder;

[0007] S2, mixing BBSCA glass powder with alumina ceramic powder, silicon nitride ceramic powder and alumina fiber in a mass ratio of 1:(0.6-1.5):(0-0.4):(0-0.1) to obtain a mixed powder, taking 100 parts by mass of the mixed powder, adding 100-400 parts by mass of a solvent and 2-4 parts by mass of a dispersant, and then adding 4-6 parts by mass of a binder, 4-6 parts by mass of a plasticizer and 0.5-1.5 parts by mass of a defoaming agent, and continuing ball milling to obtain a stable and uniform slurry;

[0008] S3, vacuum degassing the slurry obtained in step S2, casting it on a PET film, and peeling it from the PET film after drying to obtain a cast film;

[0009] S4. Cut the cast film and remove the organic additives, then sinter it under vacuum hot pressing at 800-950° C. for 2-6 hours, and cool it to obtain a high-strength low-temperature co-fired ceramic material.

[0010] Further improvement of the water-based tape casting method for preparing high-strength low-temperature co-fired ceramic materials:

[0011] Preferably, the solvent in step S2 is deionized water.

[0012] Preferably, the dispersant in step S2 is one or a combination of two or more of polyvinyl pyrrolidone, polyacrylic acid, and polyethyleneimine.

[0013] Preferably, the binder in step S2 is one or a combination of two or more of hydroxymethyl cellulose, polyvinyl alcohol, and sodium hydroxymethyl cellulose.

[0014] Preferably, the plasticizer in step S2 is one or a combination of two or more of polyvinyl alcohol, glycerol, and propylene glycol.

[0015] Preferably, the defoaming agent in step S2 is n-butanol.

[0016] Preferably, in step S3, the slurry is naturally dried at 25° C.-45° C. after being cast into a film.

[0017] Preferably, in step S4, after the cast film is cut, the temperature is slowly raised to 500-650° C. in a muffle furnace and maintained for 2-3 hours to remove organic additives.

[0018] Preferably, in step S2, the solvent and dispersant are added to the mixed powder and then ball milled for 8-16 hours, and then the binder, plasticizer and defoamer are added and the ball milling is continued for 8-16 hours.

[0019] A second object of the present invention is to provide a high-strength, low-temperature co-fired ceramic material prepared by the water-based tape-casting preparation method of any of the high-strength, low-temperature co-fired ceramic materials described above.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) The present invention provides a water-based tape casting preparation method for high-strength, low-temperature co-fired ceramic materials. The preparation method selects BBSCA glass powder and high-strength alumina ceramic powder to mix (silicon nitride ceramic powder and alumina fiber can also be added), adds water as the only solvent in the tape casting process, and adds dispersant, plasticizer, binder and defoamer, and ball mills to make a uniform slurry suitable for tape casting. After degassing, tape casting and drying, a uniform and smooth tape casting film is obtained. After vacuum hot pressing and solid phase sintering, a high-strength, low-temperature co-fired ceramic material can be obtained. Since the solvent is only water, the production process has low cost, little environmental pollution, is harmless to human health, and is suitable for large-scale factory production. It overcomes the problem that non-aqueous tape casting processes usually require the use of a large amount of toxic organic solvents, which not only has high production costs, but also pollutes the environment, harms human health, and is not conducive to industrial production.

[0022] (2) The process of the present invention is simple to operate and the conditions are easy to control. The cast film dries quickly and is completely dried without cracks after ventilation drying for 0.5-1h at 25°C-45°C, and is suitable for industrial continuous production. The cast film has good strength and flexibility and can be cut and bent at will. The low-temperature co-fired ceramic material prepared by the present invention has a flexural strength in the range of 220-420MPa, a thermal conductivity in the range of 5-11W / (m·K), and a thermal expansion coefficient that matches that of silicon components, and has great application prospects in the field of electronic packaging materials and their manufacturing. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.

[0024] Example 1

[0025] This embodiment provides a water-based tape-casting preparation method for a high-strength low-temperature co-fired ceramic material, which specifically includes the following steps:

[0026] S1. Weigh bismuth trioxide, boron oxide, silicon dioxide, copper oxide, and aluminum oxide in a molar ratio of 1:0.1:0.1:0.4:0.1, mix and ball-mill evenly, keep at 600° C. for 2 h, cool naturally, and ball-mill into powder to obtain BBSCA glass powder;

[0027] S2, BBSCA glass powder was mixed with alumina ceramic powder, silicon nitride ceramic powder and alumina fiber in a mass ratio of 1:0.6:0.3:0.05 to obtain a mixed powder, 100 parts by mass of the mixed powder was added, 100 parts by mass of a solvent (deionized water) and 2 parts by mass of a dispersant (polyvinyl pyrrolidone) were added, and the mixture was ball-milled for 8 h, and then 4 parts by mass of a binder (hydroxymethyl cellulose), 4 parts by mass of a plasticizer (polyethylene glycol) and 0.5 parts by mass of a defoaming agent (n-butanol) were added, and the ball-milling was continued for 16 h to obtain a stable and uniform slurry;

[0028] S3, vacuum degassing the slurry obtained in step S2 and casting the film on a PET film, and the cast film is naturally dried at 45° C. and then peeled off from the PET film;

[0029] S4, cutting the cast film, placing it in a muffle furnace, slowly heating it to 500° C. and maintaining it for 2 hours, removing organic additives, and then vacuum hot pressing and sintering it at 800° C. for 2 hours, and cooling it to obtain a low-temperature co-fired ceramic sheet 1.

[0030] Example 2

[0031] This embodiment provides a water-based tape-casting preparation method for a high-strength low-temperature co-fired ceramic material, which specifically includes the following steps:

[0032] S1, weighing bismuth trioxide, boron oxide, silicon dioxide, copper oxide, and aluminum oxide in a molar ratio of 1:0.2:0.2:0.5:0.2, mixing and ball-milling them uniformly, keeping them at 650° C. for 2 h, cooling them naturally, and ball-milling them into powder to obtain BBSCA glass powder;

[0033] S2, BBSCA glass powder was mixed with alumina ceramic powder and silicon nitride ceramic powder in a mass ratio of 1:1.5:0.3 to obtain a mixed powder, 100 parts by mass of the mixed powder was added with 200 parts by mass of a solvent (deionized water) and 3 parts by mass of a dispersant (polyacrylic acid), and the mixture was ball-milled for 16 hours, and then 5 parts by mass of a binder (polyvinyl alcohol), 5 parts by mass of a plasticizer (glycerol) and 1.0 parts by mass of a defoamer (n-butanol) were added, and the ball-milling was continued for 8 hours to obtain a stable and uniform slurry;

[0034] S3, vacuum degassing the slurry obtained in step S2 and casting the film on a PET film, and the cast film is naturally dried at 35° C. and then peeled off from the PET film;

[0035] S4, cutting the cast film, placing it in a muffle furnace, slowly heating it to 550° C. and maintaining it for 2 hours, removing organic additives, and then vacuum hot pressing and sintering it at 850° C. for 2 hours, and cooling it to obtain a low-temperature co-fired ceramic sheet 2.

[0036] Example 3

[0037] This embodiment provides a water-based tape-casting preparation method for a high-strength low-temperature co-fired ceramic material, which specifically includes the following steps:

[0038] S1, weighing bismuth trioxide, boron oxide, silicon dioxide, copper oxide, and aluminum oxide in a molar ratio of 1:0.5:0.5:0.7:0.3, mixing and ball-milling, keeping at 700° C. for 2 h, cooling naturally, and ball-milling into powder to obtain BBSCA glass powder;

[0039] S2, BBSCA glass powder and alumina ceramic powder were mixed in a mass ratio of 1:0.6 to obtain a mixed powder, 100 parts by mass of the mixed powder were added with 300 parts by mass of a solvent (deionized water) and 3.5 parts by mass of a dispersant (polyethyleneimine), and the mixture was ball-milled for 10 h, and then 5 parts by mass of a binder (sodium hydroxymethyl cellulose), 5 parts by mass of a plasticizer (propylene glycol) and 1.2 parts by mass of a defoaming agent (n-butanol) were added, and the ball-milling was continued for 10 h to obtain a stable and uniform slurry;

[0040] S3, vacuum degassing the slurry obtained in step S2 and casting the film on a PET film, and the cast film is naturally dried at 30° C. and then peeled off from the PET film;

[0041] S4, cutting the cast film, placing it in a muffle furnace, slowly heating it to 600° C. and maintaining it for 2 hours, removing organic additives, and then vacuum hot pressing and sintering it at 900° C. for 2 hours, and cooling it to obtain a low-temperature co-fired ceramic sheet 3.

[0042] Example 4

[0043] The embodiment provides a water-based tape-casting preparation method of a high-strength low-temperature co-fired ceramic material, which specifically comprises the following steps:

[0044] S1. Weigh bismuth trioxide, boron oxide, silicon dioxide, copper oxide, and aluminum oxide in a molar ratio of 1:1:1:1:0.5, mix and ball-mill evenly, keep at 800° C. for 2 h, cool naturally, and ball-mill into powder to obtain BBSCA glass powder;

[0045] S2, BBSCA glass powder and alumina ceramic powder, silicon nitride ceramic powder and alumina fiber are mixed in a mass ratio of 1:0.6:0.3:0.1 to obtain a mixed powder, 100 parts by mass of the mixed powder are added with 400 parts by mass of a solvent (deionized water) and 4 parts by mass of a dispersant (polyethyleneimine), and the mixture is ball-milled for 12 hours, and then 6 parts by mass of a binder (polyvinyl alcohol), 6 parts by mass of a plasticizer (polyethylene glycol) and 1.5 parts by mass of a defoamer (n-butanol) are added, and the ball-milling is continued for 12 hours to obtain a stable and uniform slurry;

[0046] S3, vacuum degassing the slurry obtained in step S2 and casting the film on a PET film, and the cast film is naturally dried at 25° C. and then peeled off from the PET film;

[0047] S4, after cutting the cast film, place it in a muffle furnace and slowly heat it to 650° C. and keep it for 2 hours, remove the organic additives, then vacuum hot press sinter it at 950° C. for 2 hours, and cool it to obtain a low-temperature co-fired ceramic sheet 4.

[0048] Example 5

[0049] The embodiment provides a water-based tape-casting preparation method of a high-strength low-temperature co-fired ceramic material, which specifically comprises the following steps:

[0050] S1, weighing bismuth trioxide, boron oxide, silicon dioxide, copper oxide, and aluminum oxide in a molar ratio of 1:0.3:0.5:0.6:0.25, mixing and ball-milling, keeping at 700° C. for 2 h, cooling naturally, and ball-milling into powder to obtain BBSCA glass powder;

[0051] S2, BBSCA glass powder and alumina ceramic powder, alumina fiber are mixed in a mass ratio of 1:0.6:0.05 to obtain a mixed powder, 100 parts by mass of the mixed powder are added with 200 parts by mass of a solvent (deionized water) and 3 parts by mass of a dispersant (polyethyleneimine), and the mixture is ball-milled for 12 hours, and then 5 parts by mass of a binder (polyvinyl alcohol), 5 parts by mass of a plasticizer (polyethylene glycol) and 1 part by mass of a defoamer (n-butanol) are added, and the ball-milling is continued for 12 hours to obtain a stable and uniform slurry;

[0052] S3, vacuum degassing the slurry obtained in step S2 and casting the film on a PET film, and the cast film is naturally dried at 25° C. and then peeled off from the PET film;

[0053] S4, cutting the cast film, placing it in a muffle furnace, slowly heating it to 600° C. and maintaining it for 2.5 hours, removing organic additives, and then vacuum hot pressing and sintering it at 900° C. for 4 hours, and cooling it to obtain a low-temperature co-fired ceramic sheet 5.

[0054] The prepared low temperature co-fired ceramic sheets 1-5 were tested for bending resistance, thermal conductivity, thermal expansion and density properties, and the test methods are as follows:

[0055] (1) Bending performance: The three-point bending strength of the sintered sheet was measured using a universal testing machine (INSTRON 5960, Instron, USA). The sintered sheet was cut into long strips and its maximum load force was tested. The bending strength was calculated using the formula:

[0056]

[0057] Where F is the maximum load (N), L is the support span, b and d are the width and thickness of the specimen (mm), respectively. Each sample is tested 5 times and the average value is taken;

[0058] (2) Thermal conductivity: The thermal conductivity of the sintered sheet was measured using a HotDisk thermal constant analyzer (TPS2200, HotDisk AB, Sweden). The sintered sheet was sandwiched between two foams and a probe was placed under the sample. Each sample was measured three times at room temperature and the average value was taken.

[0059] (3) Thermal expansion performance: The change in the size of the sintered sheet with temperature was measured using a thermomechanical analyzer (TMA). The sample size was 4 mm × 4 mm, the sample surface was polished smooth, the temperature range was 25 to 200 °C, the heating rate was 5 °C / min, and the coefficient of thermal expansion (CTE) was calculated as follows:

[0060]

[0061] Where L0 is the initial thickness of the sample, ΔT represents the temperature change, and ΔL is the thickness change of the sample within the temperature ΔT.

[0062] (4) Density analysis: The density of the sintered sheets was tested by a densitometer (AR-150PM, Dahong, Guangdong, China), and each sample was tested 5 times to obtain the average value.

[0063] After testing, the test results of the low-temperature co-fired ceramic sheet 1 are as follows: the bending strength is 331.13Mpa, the thermal conductivity is 10.61W / mk, the thermal expansion coefficient is 6.21ppm / ℃, and the density is 4.23g / cm 3 ,From the test results, it can be known that this example has produced a material with high mechanical properties, good thermal conductivity, and a thermal expansion coefficient that is well matched with the semiconductor material silicon.

[0064] After testing, the test results of the low-temperature co-fired ceramic sheet 2 are as follows: the bending strength is 266.75Mpa, the thermal conductivity is 9.76W / mk, the thermal expansion coefficient is 5.95ppm / ℃, and the density is 3.95g / cm 3 ,From the test results, it can be known that this example has produced a material with high mechanical properties, good thermal conductivity, and a thermal expansion coefficient that is well matched with the semiconductor material silicon.

[0065] After testing, the test results of the low-temperature co-fired ceramic sheet 3 are as follows: the bending strength is 226.13Mpa, the thermal conductivity is 9.49W / mk, the thermal expansion coefficient is 5.46ppm / ℃, and the density is 3.54g / cm 3 ,From the test results, it can be known that this example has produced a material with high mechanical properties, good thermal conductivity, and a thermal expansion coefficient that is well matched with the semiconductor material silicon.

[0066] After testing, the test results of the low-temperature co-fired ceramic sheet 4 are as follows: the bending strength is 288.63Mpa, the thermal conductivity is 8.64W / mk, the thermal expansion coefficient is 5.12ppm / ℃, and the density is 4.14g / cm 3 ,From the test results, it can be known that this example has produced a material with high mechanical properties, good thermal conductivity, and a thermal expansion coefficient that is well matched with the semiconductor material silicon.

[0067] After testing, the test results of the low-temperature co-fired ceramic sheet 5 are as follows: the bending strength is 254.36Mpa, the thermal conductivity is 9.35W / mk, the thermal expansion coefficient is 5.57ppm / ℃, and the density is 3.86g / cm 3 ,From the test results, it can be known that this example has produced a material with high mechanical properties, good thermal conductivity, and a thermal expansion coefficient that is well matched with the semiconductor material silicon.

[0068] Those skilled in the art should understand that the above are only some specific embodiments of the present invention, rather than all embodiments. It should be noted that for those of ordinary skill in the art, many modifications and improvements can be made, and all modifications or improvements that do not exceed the scope of protection of the present invention should be regarded as the scope of protection of the present invention.

Claims

1. A water-based tape-casting method for preparing a high-strength low-temperature co-fired ceramic material, characterized in that: The steps include: S1. Weigh bismuth trioxide, boron oxide, silicon dioxide, copper oxide and aluminum oxide in a molar ratio of 1:(0.1-1):(0.1-1):(0.4-1):(0.1-0.5), mix and ball-mill evenly, then keep at 600-800° C. for 1-4 h, and ball-mill into powder after natural cooling to obtain BBSCA glass powder; S2, mixing BBSCA glass powder with alumina ceramic powder, silicon nitride ceramic powder and alumina fiber in a mass ratio of 1:(0.6-1.5):(0-0.4):(0-0.1) to obtain a mixed powder, taking 100 parts by mass of the mixed powder, adding 100-400 parts by mass of a solvent and 2-4 parts by mass of a dispersant, and then adding 4-6 parts by mass of a binder, 4-6 parts by mass of a plasticizer and 0.5-1.5 parts by mass of a defoaming agent, and continuing ball milling to obtain a stable and uniform slurry; S3, vacuum degassing the slurry obtained in step S2, casting it on a PET film, and peeling it from the PET film after drying to obtain a cast film; S4. Cut the cast film and remove the organic additives, then sinter it under vacuum hot pressing at 800-950° C. for 2-6 hours, and cool it to obtain a high-strength low-temperature co-fired ceramic material.

2. The water-based tape casting method for preparing high-strength low-temperature co-fired ceramic material according to claim 1, characterized in that: The solvent in step S2 is deionized water.

3. The water-based tape casting method for preparing high-strength low-temperature co-fired ceramic material according to claim 1, characterized in that: The dispersant in step S2 is one or a combination of two or more of polyvinyl pyrrolidone, polyacrylic acid, and polyethyleneimine.

4. The water-based tape casting method for preparing high-strength low-temperature co-fired ceramic material according to claim 1 or 2, characterized in that: The binder in step S2 is one or a combination of two or more of hydroxymethyl cellulose, polyvinyl alcohol, and sodium hydroxymethyl cellulose.

5. The water-based tape casting method for preparing high-strength low-temperature co-fired ceramic material according to claim 1 or 2, characterized in that: The plasticizer in step S2 is one or a combination of two or more of polyvinyl alcohol, glycerol, and propylene glycol.

6. The water-based tape casting method for preparing high-strength low-temperature co-fired ceramic material according to claim 1, characterized in that: The defoaming agent in step S2 is n-butanol.

7. The water-based tape casting method for preparing high-strength low-temperature co-fired ceramic material according to claim 1, characterized in that: In step S3, the slurry is cast into a film and then naturally dried at 25°C-45°C.

8. The water-based tape casting method for preparing high-strength low-temperature co-fired ceramic material according to claim 1, characterized in that: In step S4, after the cast film is cut, the temperature is slowly raised to 500-650° C. in a muffle furnace and maintained for 2-3 hours to remove organic additives.

9. The water-based tape-casting preparation method of the high-strength low-temperature co-fired ceramic material according to claim 1, characterized in that: In step S2, a solvent and a dispersant are added to the mixed powder, followed by ball milling for 8-16 hours, and then a binder, a plasticizer and a defoaming agent are added and ball milling is continued for 8-16 hours.

10. A high-strength, low-temperature co-fired ceramic material obtained by the water-based tape casting preparation method of the high-strength, low-temperature co-fired ceramic material according to any one of claims 1 to 9.